Ontology engineering - Forbes, David; Wongthongtham, Pornpit; Terblanche, C.; Pakdeetrakulwong, U. (2018)
Some ontologies represent domain knowledge and organise knowledge into a specific structure e.g. hierarchy, graph, etc. Other ontologies represent formal vocabularies with well-defined axioms that allow further deductions or inferences.